FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Maftukhah, 14.05.52.0225; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of profitability, solvency,the auditor’s opinion, firm size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange. The independent variabel in this study consisted of profitability, solvability and auditor. Audit delay as the dependent variable, and company size as a moderating variable. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017. The research sample was 188 companies. This research method uses purposive sampling. Data analysis using Multiple Linear Regression with the SPSS 19 program. The results of this study indicate that profitability has a negative and not significant effect on audit delay, solvency has a significant positive effect on audit delay, auditor opinion has a significant negative effect, firm size does not moderate profitability towards audit delay, company size weakens solvency to audit delay, company size does not moderate the auditor's opinion on audit delay.